WORKING WITH DIGITAL INFORMATION ON A COMPUTER - Nargiza Dilmurodovna Mirzahmedova (Scholar Express Journal, 2022)
In the article, we consider the coding of information, which is directly related to the development of digital technology. In modern educational institutions, the topic of information coding is studied as the most famous topic. Today, the basis of this process is the study of various properties of computers.
Keywords: Coding; Digitization; Coding Of Text Information; Frequency